Trends and Research Directions in Perioperative Antibiotic Use: A Bibliometric Study (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2025)
The problem of antibiotic resistance has developed as a growing global health problem that substantially impacts the surgical site infections (SSIs). Perioperative antibiotics should be used in the prevention of surgical site infections; however, misuse of antibiotics can affect antibiotic resistance. This research paper aims to discuss the trends and the research directions of studying the use of perioperative antibiotics through bibliometric analysis with respect to detecting the trends in publishing, topic development, and future research directions. A systematic literature review (SLR) was conducted using 67 papers retrieved in the Web of Science database. R Studio and VOSviewer were used to analyze data to describe trends in the field of publications, collaboration of scholars, and the development of keywords. The information demonstrates that the research regarding the use of antibiotics during perioperative has increased significantly over time since 2015, which proves to be a primary focus of the prevention of surgical site infections (SSI). A double shift observed in bibliometric analysis was the focus of research towards prevention and more focused and evidence-based antibiotic treatment. The problem of antibiotic resistance emerged as one of the central themes that were based on such aspects as the time of treatment, the type of antibiotic, and adherence to clinical standards. The cartographic analysis demonstrated the development streams of research in the past two decades. This study emphasizes the increasing significance of perioperative antibiotic administration in the prevention of surgical site infections and illustrates the pressing necessity for evidence-based guidelines. It also delineates essential avenues for future research, encompassing the optimization of antibiotic prophylaxis, measures to mitigate resistance, adherence to therapeutic procedures, and socio-economic factors in perioperative antibiotic management.